Impact of Electronic Information Sources on the Academic Users in Mysore: an Analytical Study - Chowdappa, N.; Chandrashekara, M.; Ramasesh, C. P. (Journal of Information and Knowledge, 2013)
The paper depicts the extent of dependency of users of educational and research institutions of Mysore city on the electronic/digital media. The responses of 1000 users and the critical evaluation of 24 subject experts under Delphi study have been gathered to render valid findings and suggestions. The attempt clearly shows the degree of the use of digital information resources vis-à-vis the conventional print media.